1997
DOI: 10.1046/j.1526-4610.1997.3709583.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Chronic Posttraumatic Headache

Abstract: Patients with PTH have reduced regional cerebral blood flow, and regional and hemispheric asymmetries. These cerebral hemodynamic alterations support an organic basis to chronic posttraumatic headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 15 publications
0
40
0
2
Order By: Relevance
“…Tentou-se estabelecer uma base orgânica para a sintomatologia decorrente do pós-trauma, incluindo a cefaleia. Há estudos de imagem descrevendo lesões parenquimatosas, diminuição de fluxo sanguíneo cerebral após trauma, com zonas focais de perfusão diminuída e também alterações metabólicas 8,9 . Dor neuropática está tipicamente associada à lesões nervosas consequentes ao trauma, inflamação, isquemia ou outros mecanismos.…”
Section: Discussionunclassified
“…Tentou-se estabelecer uma base orgânica para a sintomatologia decorrente do pós-trauma, incluindo a cefaleia. Há estudos de imagem descrevendo lesões parenquimatosas, diminuição de fluxo sanguíneo cerebral após trauma, com zonas focais de perfusão diminuída e também alterações metabólicas 8,9 . Dor neuropática está tipicamente associada à lesões nervosas consequentes ao trauma, inflamação, isquemia ou outros mecanismos.…”
Section: Discussionunclassified
“…17 Single-photon emission computed tomography (SPECT) has shown decreased cerebral blood flow and abnormally asymmetrical regional blood flow. 18 Brain auditory evoked responses revealed alteration and prolonged latency of some components. 19 PET showed a decrease in the metabolic rate of glucose, and other studies revealed release of inhibitory neurotransmitters and excitatory amino acids.…”
Section: Clinical Featuresmentioning
confidence: 98%
“…Previous research suggests underlying pathophysiological similarities of migraines and PTH [6][7][8]. The cortical spreading depression associated with migraine is commonly recognized as the electrophysiological substrate of this primary headache disorder [9].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Intracellular sodium, calcium, and chloride in addition to extracellular potassium are all elevated in neurons after head trauma and during migraine exacerbations. Furthermore, both migraine and mTBI result in an excess release of opioids and excitatory amino acids, such as beta-endorphins and glutamate, respectively [6,11].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation